2016
DOI: 10.1038/cddis.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

A long non-coding RNA interacts with Gfra1 and maintains survival of mouse spermatogonial stem cells

Abstract: Spermatogonial stem cells (SSCs) are unique male germline stem cells that support spermatogenesis and male fertility. Long non-coding RNAs (lncRNA) have been identified as key regulators of stem cell fate; however, their role in SSCs has not been explored. Here, we report that a novel spermatogonia-specific lncRNA (lncRNA033862) is essential for the survival of murine SSCs. LncRNA033862 is expressed in early spermatogonia including SSC and was among 805 lncRNAs identified by global expression profiling as resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 58 publications
2
48
1
Order By: Relevance
“…Interestingly, the strong enrichment PI3K-Akt pathway, which was observed in the highly co-expressed mRNAs and lncRNAs of SSCs and FGSCs (Supplementary Figure 4), suggests that FGSCs had a similar GDNF signaling mechanism as SSCs. To determine whether FGSCs had the same GDNF signaling mechanism as SSCs, we removed GDNF from the culture medium for a period of 7 days and found that the results were similar to those of a previous study on SSCs [64]. Withdrawal of GDNF for a week resulted in a significant reduction in cell numbers (of 1.0 × 10 5 plated cells, an average of 0.4×10 5 remained after GDNF depletion) (Figure 4C–4E).…”
Section: Resultssupporting
confidence: 79%
“…Interestingly, the strong enrichment PI3K-Akt pathway, which was observed in the highly co-expressed mRNAs and lncRNAs of SSCs and FGSCs (Supplementary Figure 4), suggests that FGSCs had a similar GDNF signaling mechanism as SSCs. To determine whether FGSCs had the same GDNF signaling mechanism as SSCs, we removed GDNF from the culture medium for a period of 7 days and found that the results were similar to those of a previous study on SSCs [64]. Withdrawal of GDNF for a week resulted in a significant reduction in cell numbers (of 1.0 × 10 5 plated cells, an average of 0.4×10 5 remained after GDNF depletion) (Figure 4C–4E).…”
Section: Resultssupporting
confidence: 79%
“…It is clear from such studies that the transcriptome levels of lncRNAs are greater than those of mRNAs during spermatogenesis and that the expression of lncRNAs is also dynamically regulated. Mechanistic details of lncRNA function during spermatogenesis have been provided by only a few studies, including our report of the role of mrhl RNA in regulation of Wnt signaling through p68 RNA helicase (27,(44)(45)(46). The present report describes a new dimension in the context of spermatogenesis, with lncRNA regulating the expression of an important transcription factor and such regulation being crucial for meiotic entry or spermatogonial differentiation.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, it has become clear that serval types of ncRNAs, involving miRNA, lncRNA, piRNA, small nucleolar RNA, and circRNAs, play important roles in stem cell self‐renewal by forming complicated epigenetic regulatory networks together with other epigenetic factors related to DNA methylation, histone methylation, and acetylation (Dupuis‐Sandoval, Poirier, & Scott, ; S. Hu & Shan, ; Rojas‐Rios, Chartier, Pierson, & Simonelig, ; C. Y. Yu et al, ; Z. Yu, Li, Fan, Liu, & Pestell, ). As for SSCs, although a large number of ncRNAs have been screened as potential regulatory molecules for SSC self‐renewal using high‐throughput RNA sequencing and bioinformatics approaches, only a small portion of them have been validated and functionally characterized using biological experiment to uncover roles in SSCs self‐renewal, particularly lncRNAs, piRNA, and circRNAs (K. Hu et al, ; Li et al, ; X. Li, Ao, et al, ), thus there is an urgent need to reveal more ncRNAs associated with SSC self‐renewal to elucidate the molecular mechanisms underlying SSC self‐renewal. Encouragingly, great improvements of technologies have been recently made on isolation, characterization, in vitro culture, and in vivo transplantation of SSCs will provide us a robust research platform to explore the function of ncRNAs in SSC self‐renewal (X. Li, Ao, et al, ; Mulder et al, ; Takashima & Shinohara, ; Zhang, Sun, & Zou, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that lncRNAs are important players in diverse cellular processes including proliferation, differentiation, apoptosis, senescence, stress response through complicated mechanisms involving lncRNA–mRNA, lncRNA–miRNA, lncRNA–DNA, and lncRNA–protein interaction (Fatica & Bozzoni, ), although in vivo functional characterization of lncRNA are still facing many challenges, for instance, some of lncRNA mutant mice do not exhibit a severe or expected phenotype similar to that of in vitro experiments (Bassett et al, ; Kohtz, ; S. Nakagawa, ). To date, some lncRNAs have been demonstrated to play critical regulatory roles in posttranscriptional and transcriptional regulation in self‐renewal of stem cell, including SSCs (Lee et al, ; Li et al, ).…”
Section: Ncrna In Sscs Self‐renewalmentioning
confidence: 99%
See 1 more Smart Citation